2009
DOI: 10.1109/led.2009.2020182
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity of Graphene Nanoribbon Interconnects

Abstract: Abstract-Graphene nanoribbon interconnects are fabricated, and the extracted resistivity is compared to that of Cu. It is found that the average resistivity at a given line-width (18nm Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
100
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(109 citation statements)
references
References 15 publications
5
100
0
3
Order By: Relevance
“…Due to its high electron mobility and high thermal conductivity, graphene and few-layer graphene (FLG) are considered promising for applications in field-effect transistors [7], interconnects [8][9], thermal interface materials [10][11], and heat spreaders [12][13][14].…”
mentioning
confidence: 99%
“…Due to its high electron mobility and high thermal conductivity, graphene and few-layer graphene (FLG) are considered promising for applications in field-effect transistors [7], interconnects [8][9], thermal interface materials [10][11], and heat spreaders [12][13][14].…”
mentioning
confidence: 99%
“…The superior electrical conductivity of graphene, for example, has been exploited to create interconnects for nanoelectronic circuits that outperform their copper counterparts. 1,2 Going forward, the challenge in leveraging these materials for commercial applications is twofold: First is the ability to devise methods of synthesis that are scalable and controllable; second, and equally important, is the ability to characterize the properties of the synthesized nanostructures, which often differ significantly from the properties of bulk materials. Materials characterization at the nanoscale requires the atomic spatial resolution possible with techniques such as atomic force microscopy, electron microscopy, X-ray diffraction, and others.…”
mentioning
confidence: 99%
“…It has been observed that multilayer graphene has a greater Seebeck coefficient compared to single layer graphene up to S=54µV/K [25]. For a low-defect CHNF, the upper limit of resistivity can be estimated using that observed for GNR ρ = 0.35 µΩ m [26]. This experimental result for GNR corresponds to the highest resistivity observed in that study, which maximizes the effect of edges.…”
Section: Thermal Transport Simulationmentioning
confidence: 52%